Stoichiometric imbalance and microbial community regulate microbial elements use efficiencies under nitrogen addition - Li, Jing; Sang, Changpeng; Yang, Jingyi; Qu, Lingrui; Xia, Zongwei; Sun, Hao; Jiang, Ping; Wang, Xugao; He, Hongbo; Wang, Chao (Soil biology & biochemistry, 2021)
Microbial elements use efficiencies are the important parameters in regulating soil carbon (C) and nitrogen (N) mineralization processes. Microbial C use efficiency (CUE) describes the proportion of C used for growth relative to the total organic C uptake. As such, high CUE values mean relatively less CO2 emission and more C retention in microbial biomass. Similarly, a higher microbial N use efficiency (NUE) indicates efficient biomass N sequestration and less N mineralization. However, very little is known how the microbial CUE and NUE are affected by N enrichment in forest soils. Here, we studied soil microbial CUE and NUE simultaneously using 18O-water tracer approach in a long-term N addition experiment comprising control (atmospheric N deposition, 2.7 g N m−2 yr−1), low N addition (atmospheric N deposition + 2.5 g N m−2 yr−1) and high N addition (atmospheric N deposition + 7.5 g N m−2 yr−1) in a temperate forest. We found microbial CUE responses to N addition were dependent on N addition rates and soil horizons. Specifically, low N addition significantly increased the microbial CUE by 45.12% while high N addition significantly reduced it by 27.84% in organic soil. Further, mineral soil microbial CUE did not change under low N addition but significantly increased by 133.18% under high N addition. We also found microbial NUE decreased with increasing N addition rate in organic soil but showed an opposite pattern in mineral soil. The stoichiometric imbalances associated with phosphorus between microbial biomass and resources and the microbial community changes under N addition were correlated with microbial CUE and NUE. Further, N addition decreased microbial biomass turnover in organic soil but accelerated it in mineral soil. Altogether, our results indicated that N addition could control soil C and N cycling processes by affecting microbial elements use efficiencies (i.e. CUE and NUE), which may consequently impact C and N sequestration in this temperate forest soil. •Higher N depressed microbial growth in organic soil but promoted it in mineral soil.•N addition declined microbial NUE in organic soil but increased it in mineral soil.•Microbial CUE was non-linearly correlated with microbial NUE.•Shifts in microbial community composition affected microbial CUE and NUE.